Memes against sexism? A multi-method analysis of the feminist protest hashtag #distractinglysexy and its resonance in the mainstream news media. (June 2020) - Brantner, Cornelia; Lobinger, Katharina; Stehling, Miriam
Hashtag feminism has become a popular tactic of online protest against gender inequality. Using the Twitter hashtag #distractinglysexy, women scientists posted pictures of themselves in labs or during field research to contest misogynist remarks by Nobel laureate Tim Hunt. We examined the resulting humorous and memetic discourse on Twitter as well as its coverage in news media combining a content analysis of the multimodal tweets with a qualitative discourse analysis of German and British news media. The results show that the ironic memes in which researchers addressed sexism in academia by parodying social norms and ideals of 'sexiness' yielded substantial media attention, but with differences in the two countries: While the hashtag #distractinglysexy initiated a broader debate on sexism and discrimination in academia in the UK news media discourse, in the German context, this form of 'self-mediation' was portrayed either as 'something funny on the Web' or as a harmful firestorm.